2015
DOI: 10.1016/j.jadohealth.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Association Between Overvaluation of Weight and Binge Eating Among Overweight Adolescent Girls

Abstract: Purpose We investigated whether overvaluation of weight, defined as having a high degree of concern with weight such that it unduly influences self-evaluation, was prospectively associated with binge eating onset among overweight adolescent girls and whether overvaluation of weight signaled greater impairment among those with weekly binge eating. Methods We used generalized estimating equations to assess the prospective association between weight overvaluation at time 1 and the onset of weekly binge eating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Body dissatisfaction or shape and weight concerns, which may fluctuates based on factors such as recent eating behaviors and mood, often are linked with overvaluation of shape and weight—the degree to which one’s self-esteem is highly contingent on shape and/or weight, which is a more stable construct and is considered the core psychopathology of EDs [18]. Approximately 25% of adolescent girls with overweight/obesity overvalue shape and weight and it is a prospective risk factor for development of eating disorder behaviors [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Body dissatisfaction or shape and weight concerns, which may fluctuates based on factors such as recent eating behaviors and mood, often are linked with overvaluation of shape and weight—the degree to which one’s self-esteem is highly contingent on shape and/or weight, which is a more stable construct and is considered the core psychopathology of EDs [18]. Approximately 25% of adolescent girls with overweight/obesity overvalue shape and weight and it is a prospective risk factor for development of eating disorder behaviors [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in body image are increasingly being recognised as a public health concern, being associated with poor quality of life (Griffiths et al, 2016) as well as increased risk for a range of difficulties, most notably eating disorders, but also depressive symptoms, overweight, and unhealthy weight control behaviours, such as cigarette smoking (Field et al, 2005; Loth, Watts, Van Den Berg, & Neumark-Sztainer, 2015; Patalay, Sharpe, & Wolpert, 2015; Rohde, Stice, & Marti, 2015; Sonneville et al, 2012; Sonneville et al, 2015). Despite the centrality of body image disturbances in models of risk and maintenance (e.g., Fairburn, Cooper, & Shafran, 2003; Stice, Gau, Rohde, & Shaw, 2017), and in diagnostic criteria for eating disorders (American Psychiatric Association, 2013), this construct remains relatively loosely conceptualised, with terms often used interchangeably, or captured under umbrella concepts, such as ‘weight and shape concerns’ (e.g., La Mela et al, 2015; Murphy, Dooley, Menton, & Dolphin, 2016).…”
mentioning
confidence: 99%
“…Eating, weight, and shape overconcern were linked to the onset of partial-and full-syndrome EDs at 3-year followup in college-aged women [72]. Further, prospective findings from the Growing Up Today cohort study revealed that overconcern at baseline predicted weekly binge eating in adolescent girls [73], with complementary findings suggesting the protective value of body satisfaction against frequent binge eating in overweight girls [74]. However, recent findings in adolescent boys and young men from the same cohort reveal that body image concerns related to physique did not predict EDs but rather predicted subsequent substance abuse including steroids, illicit drugs, and alcohol [75], which underscores the importance of recognizing sex-specific clinical profiles associated with weight and shape overconcern.…”
Section: Cognitive Behavioral and Emotional Ed Risk Factorsmentioning
confidence: 92%
“…Further, there is recent cross-sectional support for a positive relationship between weight overconcern and depression severity [73]. However, the directionality of the relationship between depressive symptoms and EDs remains variable.…”
Section: Cognitive Behavioral and Emotional Ed Risk Factorsmentioning
confidence: 99%